1990
DOI: 10.1002/actp.1990.010410404
|View full text |Cite
|
Sign up to set email alerts
|

Semicontinuous emulsion polymerization of vinyl acetate. VIII. Copolymerization with di‐2‐ethylhexyl maleate

Abstract: The semicontinuous emulsion copolymerization of vinyl acetate with 2-ethylhexyl maleate has been studied. The amount of polymer obtained during the continuous addition ot comonomers increases at first nonlinearly than linearly with time. During this period the viscosity of the obtained emulsion is not proportional t o the polymer content. The conversions are affected by the reaction conditions, e.g. the stirring rate and the amount of the transfer agent nbutanol and its distribution between the initial reactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 34 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Thus, Donescu et al 10 reported that, in semicontinuous polymerization, an increasing agitation rate led to an increase of both the induction period and the final conversion. Thus, Donescu et al 10 reported that, in semicontinuous polymerization, an increasing agitation rate led to an increase of both the induction period and the final conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Donescu et al 10 reported that, in semicontinuous polymerization, an increasing agitation rate led to an increase of both the induction period and the final conversion. Thus, Donescu et al 10 reported that, in semicontinuous polymerization, an increasing agitation rate led to an increase of both the induction period and the final conversion.…”
Section: Introductionmentioning
confidence: 99%